Badania przemian japońskiego filmu awangardowego. Od Terayamy do audiowizualnego eksperymentu po 2000 roku - Kiejziewicz, Agnieszka (Studia Azjatystyczne, 2017)
The presented article covers the subject of changes in the Japanese avant garde film through the cinematographic epochs. The aim of the paper is to introduce the reader to the methodology, definitions and the range of the research concerning Japanese avant-garde cinema. The author also presents the importance of the conducted research for the Polish film research. What is more, she tries to answer the question of how the avant-garde film should be perceived in the era of mass-media.